2014
DOI: 10.1371/journal.pone.0104979
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Tumor Molecular Heterogeneity in Histopathological Diagnosis

Abstract: BackgroundDetection of molecular tumor heterogeneity has become of paramount importance with the advent of targeted therapies. Analysis for detection should be comprehensive, timely and based on routinely available tumor samples.AimTo evaluate the diagnostic potential of targeted multigene next-generation sequencing (TM-NGS) in characterizing gastrointestinal cancer molecular heterogeneity.Methods35 gastrointestinal tract tumors, five of each intestinal type gastric carcinomas, pancreatic ductal adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…2932 It has also been shown that molecular heterogeneity of tumors is reflected in corresponding morphologic heterogeneity on tissue slides. 3335 The ability to ‘unlock’ subtle, sub-visual attributes of tumors from tissue slides via computerized image analysis offers the opportunity to glean a wealth of information regarding morphologic heterogeneity compared with what may be discerned via traditional visual (or manual) inspection of slides alone.…”
Section: Discussionmentioning
confidence: 99%
“…2932 It has also been shown that molecular heterogeneity of tumors is reflected in corresponding morphologic heterogeneity on tissue slides. 3335 The ability to ‘unlock’ subtle, sub-visual attributes of tumors from tissue slides via computerized image analysis offers the opportunity to glean a wealth of information regarding morphologic heterogeneity compared with what may be discerned via traditional visual (or manual) inspection of slides alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, few correlation studies of morphological classification and molecular characteristics have been carried out [77,78] and pathologists should be aware of their pivotal role in this field. In-depth studies combining molecular features with histopathological and IHC profiles may reveal interesting associations and are currently feasible, thanks to new molecular profiling technologies, generating accurate molecular information from formalin-fixed and paraffin-embedded tissues [56,79]. On this note, Setia et al [80] have recently proposed a practical algorithm based on IHC and in situ hybridisation techniques currently available in routine diagnostic practice.…”
Section: Moving Towards Molecular Subtyping and Precision Medicinementioning
confidence: 99%
“…In this series, FHIT rearrangements observed in PDACs were only in part validated in adjacent PanINs [23]. However, this might be related to molecular heterogeneity observed in PDAC (and therefore in PDAC-associated pre-invasive lesions) [46]. Of note, PanIN lesions are characterized by chromosomal instability [4750], and therefore the down-regulation of Fhit expression we observed in our series may be associated with FHIT gene loss rather than with epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%